Necrotizing enterocolitis in a neonate with severe congenital pulmonary valve stenosis complicated by a postoperative right atrial thrombus: a case report - Zhang, Wenjing; Zhang, Li; Liu, Haiting (Frontiers in Pediatrics, 2025)
Congenital heart disease may increase the incidence of necrotizing enterocolitis, especially in low-birth-weight infants. We report a case of a newborn with pulmonary valve stenosis who developed neonatal necrotizing enterocolitis IIIB. The infant underwent initial cardiac surgery followed by a laparotomy. After cardiac surgery, a right atrial thrombus was found by cardiac ultrasound. Enterococcus faecium was identified using metagenomic next-generation sequencing of ascitic fluid. The infant received targeted antibiotic therapy and anticoagulant treatment and was then discharged.